2017
DOI: 10.1177/0363546517695789
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Arthroscopic Rotator Cuff Repair With a Transosseous Suture Technique: A Prospective Randomized Controlled Trial

Abstract: No significant differences were found between the 2 arthroscopic repair techniques in terms of functional and radiological results. However, postoperative pain decreased more quickly after the transosseous procedure, which therefore emerges as a possible improvement in the surgical repair of the rotator cuff. Registration: NCT01815177 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 56 publications
(110 reference statements)
0
38
1
12
Order By: Relevance
“…Suture cut-thorough of bone was only exceptionally observed 2, 7. Randelli et al 14 . demonstrated for the first time in a randomized double blind clinical trial comparing arthroscopic anchorless transosseous versus anchored single-row repair similar results regarding magnetic resonance imaging–assessed tendon healing (87% vs 88% Sugaya type I-III 1 year after surgery) and shoulder function assessed by Constant score, QuickDASH, and pain score.…”
Section: Discussionmentioning
confidence: 91%
“…Suture cut-thorough of bone was only exceptionally observed 2, 7. Randelli et al 14 . demonstrated for the first time in a randomized double blind clinical trial comparing arthroscopic anchorless transosseous versus anchored single-row repair similar results regarding magnetic resonance imaging–assessed tendon healing (87% vs 88% Sugaya type I-III 1 year after surgery) and shoulder function assessed by Constant score, QuickDASH, and pain score.…”
Section: Discussionmentioning
confidence: 91%
“…In a cadaver study conducted by Kilcoyne et al in 2017, transosseous repair was noted to be superior to other techniques in the miniopen treatment method (22). Recently, arthroscopic studies have shown that transosseous repair provides good functional results (23)(24)(25). In 2016, Flanagin et al published the successful mid-term results of transosseous repair in 109 patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since April 2015, we have used PGA threads for mattress sutures to gain the initial cuff securing force and avoid excessive tension on the rotator cuff. In addition to our method, other methods for arthroscopic transosseous repair of the rotator cuff without implant using an ArthroTunneler [5][6][7][8][9][10] , hollow needle [11][12][13] , special equipment [14][15] , and anterior cruciate ligament guide [16] have been reported. However, there have been on 4 reports describing clinical outcomes from arthroscopic transosseous repair of the rotator cuff without implant in more than 50 patients [1,10,11,13] .…”
Section: Discussionmentioning
confidence: 99%